Congelamento inverso em um modelo de vidro de spin com Clusters - Silva, Cintia Fernandes da (2014)
This work analyzes a spin glass (SG) model with cluster in two versions: a classic version with Ising spins and in a fermionic version with spin operators. In this model, the basic entities are correlated clusters that interact each other disorderedly (intercluster interaction). It is also considered short-range interactions among spins belonging to the same cluster (intracluster interaction), which can be ferromagnetic (FE) or antiferro- magnetic (AF). Disordered intercluster interactions are analytically calculated by using the framework of Parisi one-step replica symmetry breaking. After this treatment, we get an effective single cluster model solved by exact diagonalization. The fermionic version of the model can introduce quantum fluctuations by means of a transverse magnetic field Γ. As a result, the linear susceptibility χ has a cusp at the transition temperature Tf and the specific heat Cv has a broad maximum at temperature T* about 20% above Tf . However, for Γ sufficiently high, this difference is greater. This behavior is observed by some authors for the compound LiHoxY1-xF4 at low concentration. Furthermore, the fermionic SG model with cluster in the grand canonical ensemble (where the chemical potential μ introduces charge fluctuations) is used to investigate the mechanisms responsible for the inverse freezing (IF). In this analysis, for a certain region of μ, a reentrance related to the inverse freezing arises. However, the increase of the FE intracluster interactions J0 can take the tricritical point to lower T, introducing a second-order IF transition. On the other hand, the Γ destroys gradually the inverse freezing. The necessary mechanisms for the emergence of inverse freezing transition are also studied using the cluster SG model in a classic version with Ising spins. This study is firstly conducted considering only firstneighbors intracluster interactions AF and in a second moment considering intracluster interactions among second neighbors, where it is possible to introduce intracluster geometrical frustration. The presence of antiferromagnetic intracluster interactions decreases the total magnetic moment of the clusters, leading to a PM phase with low entropy, favoring the appearance of inverse freezing. Moreover, the presence of geometrical frustration is contrary to the emergence of inverse freezing.